2009
DOI: 10.1002/cphc.200900018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cytidine 5′‐Monophosphate with Au(111): An In Situ Infrared Spectroscopic Study

Abstract: The interaction of cytidine 5'-monophosphate (CMP) with gold surfaces is studied by means of in situ infrared spectroscopy and cyclic voltammetry at the Au(111)|aqueous solution interface. Similar to other nucleic acid components, cytidine 5'-monophosphate is chemisorbed on the surface at positive potentials, and the amount of adsorbed CMP increases with the potential. Subtractively normalized interfacial Fourier-transform infrared spectroscopy (SNIFTIRS) is used to identify the adsorbed and desorbed species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…90 Doneux and Fojt studied cytidine adsorption onto Au(111) using in situ IR spectroscopy and concluded that chemisorption occurs via the N3 nitrogen exclusively. 98 Thymine adsorption was the weakest and was proposed to be via the C4 keto oxygen. 90 The orientation of the adsorbed bases is still under debate and mechanisms where the base ring is perpendicular, parallel or tilted with respect to the metal surface have been suggested.…”
Section: Attractive Forcesmentioning
confidence: 99%
“…90 Doneux and Fojt studied cytidine adsorption onto Au(111) using in situ IR spectroscopy and concluded that chemisorption occurs via the N3 nitrogen exclusively. 98 Thymine adsorption was the weakest and was proposed to be via the C4 keto oxygen. 90 The orientation of the adsorbed bases is still under debate and mechanisms where the base ring is perpendicular, parallel or tilted with respect to the metal surface have been suggested.…”
Section: Attractive Forcesmentioning
confidence: 99%
“…How these molecules interactw ith the NPs is af ar more complicated matter to expose. While there is extensive literature about the adsorption of bases, nucleosides and nucleotides in thin films of different metals such as gold, [45][46][47][48][49][50] silver [51,52] and even copper, [53,54] in the case of NPs studies are rather scarce. Although somea ttempts have been made to extrapolate these results to NPs, such approaches are often complicated since they tend to involve af ilm of metal being modeled like ah uge NP (with ar adius tending to infinity) and this situation is hard to correlate with reality.T he most favoured technique to perform these studies is SERS (surfaceenhanced Raman spectroscopy), because its signals trongly depends on interparticle distance.…”
Section: Interaction and Affinity Of The Monomers With Aunpsmentioning
confidence: 99%
“…This indicates that the adsorbed molecules are most likely chemisorbed rather than physisorbed. Chemisorption via the N (3) atom of the pyrimidine ring has been suggested for cytosine, and for related compounds such as cytidine and cytidine 5′-monophosphate . It is also possible that the surface state intensity and energy vary due to a change in the reconstruction of the surface from the usual herringbone structure for Au(111) or the (1 × 2) reconstruction of Au(110).…”
Section: Resultsmentioning
confidence: 99%
“…Chemisorption via the N (3) atom of the pyrimidine ring has been suggested for cytosine, 34 and for related compounds such as cytidine and cytidine 5′-monophosphate. 18 It is also possible that the surface state intensity and energy vary due to a change in the reconstruction of the surface from the usual herringbone structure for Au(111) or the (1 × 2) reconstruction of Au(110). Because alteration of the reconstruction requires a chemical interaction, this interpretation leads to the same conclusion, that chemical bonding occurs.…”
Section: Methodsmentioning
confidence: 99%